Be water: Direct and indirect relations between perceived emotional intelligence and subjective well‐being. (7th July 2014) - Vergara, Ana I.; Alonso‐Alberca, Natalia; San‐Juan, César; Aldás, Joaquín; Vozmediano, Laura
Abstract Trait emotional intelligence (TEI) has been shown to have predictive capacity for certain dimensions of adaptation, such as life satisfaction and affectivity. The Trait Meta Mood Scale (TMMS), based on the EI ability model, has been shown to have predictive capacity for subjective well‐being through its three factors (attention, clarity, and emotional repair), but little is known about the mediating role played by these dimensions, both among themselves and in relation to other variables. The aim of the present study was to analyse the direct and indirect relationships between the TMMS factors and subjective well‐being dimensions, using structural equation modelling, also including self‐efficacy in the model as a mediator of these relationships. Attention was found to have a negative effect on subjective well‐being, which was inhibited when clarity and repair were included as mediators. Self‐efficacy played a major role since it increased the positive effect of clarity and repair on subjective well‐being. This study provides evidence of the advantage of using the TMMS factors separately and of studying their mediational role in order to better understand the processes underlying the manner in which TEI influences subjective well‐being.